EVALUATION OF THE STATUS OF WATER RESOURCES AND INFRASTRUCTURE FOR COMMUNITY DEVELOPMENT IN WARWADE, DUTSE, JIGAWA STATE, NIGERIA - Tasi'u, Y. R. (FUDMA Journal of Sciences, 2023)
The Study examined the status of water resources and infrastructure for community development in Warwade town. Water scarcity and ineffective water infrastructures are among the major problems hindering community development in the area. The aim of the research was to evaluate status of waterinfrastructures. Availability sampling technique was adopted. Data was gathered using check list, selfadministered questionnaire, field observation and FGD. The data was analysed using simple statistics and Likert Scale. Findings of the research shows that most of the respondents involved in patching water are between the ages of 30 to 59. Findings on educational status indicated that 44% of the respondents attended primary school. Results indicated that majority of the respondents are farmers 24 (48%). Also result shows that there is one major dam in the area which is underutilised. Result from check list shows that there are 20 open well, 6 functioning and 14 non-functioning, 6 hand pumps 4 are functioning and 2 non-functioning. The result shows that ‘’Pipe born water was provided to the village in 2003 which is no longer functioning and prior to that time there was only one single borehole powered by electricity at Zobiya which was converted to solar’’. Similarly research findings revealed that the major source of water for the community are street open wells with 46% responses. The most popular traditional method of water management is Kwari with 60% responses. Likert scale of analysis shows that the computed means of the performance of stakeholders in the provision of water
Keywords: Community, Water Resource, Infrastructure, Rural Areas, Development